Peran Bantuan Kemanusiaan Indonesia dalam Meningkatkan Pemenuhan Kebutuhan Dasar Masyarakat di Palestina - Putriani, Amira; Apriliyano, Caca; Setiawan, Dendi; Khotimah, Kulsum (UIN Sunan Gunung Djati Bandung, 2025)
The Israeli attacks on Palestine have had a detrimental impact on the survival of Palestinian communities. One of the sufferings caused by the conflict is a humanitarian crisis experienced by the Palestinian people. Indonesia is a country that contributes to providing humanitarian aid in this conflict. Therefore, this research aims to determine the effectiveness of the humanitarian aid provided by Indonesia to Palestine. This research method utilizes a qualitative descriptive approach. Data are collected secondarily through extensive literature studies and document analysis. The results of this study show that Indonesia's assistance in meeting basic needs in Gaza, Palestine, has had a significant positive impact on sustaining life there. The impact of food aid is crucial for Palestinians who face difficulties accessing food due to blockade and conflict. Such assistance can help reduce hunger and malnutrition among the Gaza population, especially among vulnerable groups such as children and the elderly.